Мicropropagation protocol for Mongolian rare shrub Lycium truncatum Y.C. Wang - Erdenetuul, D.; Selenge, M.; Bolortuya, U.; Uyanga, B.; Altantsetseg, B.; Senthil, Kalaiselvi; Oyunbileg, Yu. (Journal of Phytology, 2024)
In this study, micropropagation protocol for the Mongolian rare shrub Lycium truncatum L. has been developed through axenical seed germination. There are successful micropropagation procedures for some Lycium species; nonetheless, L. truncatum requires both in-vitro and ex-vitro optimization.The 4-week-old sterile seedlings with spontaneous root formation, cultivated in full-strength hormone-free MS media were utilized as initial explants for in vitro culture. The highest shoot proliferation (4.6 shoots/explant) was achieved on Driver and Kuniyuki Walnut medium (DKW) supplemented with 2 mg/L kinetin (KIN) and 0.1 mg/L 1-naphtaleneacetic acid (NAA) combination. The proliferating shoots on the half-strength MS media supplemented with 0.1mg/L NAA displayed robust root formation. The rooted plantlets were acclimated in sterile soil in a pot and cultivated at room temperature for 2-3 months with a high survival rate of more than 90% before transferring to the greenhouse.